Instruções de estratégias de leitura hipertextual e língua inglesa: um estudo com aprendizes da educação tecnológica em ambiente virtual de aprendizagem - Tiraboschi, Fernanda Franco (2015)
This study examines the effects of cognitive and metacognitive reading strategies on the reading skills of English language learners. We focused on strategies that enable learners to develop self-monitoring activities for comprehending hypertext in English. We were motivated to conduct this research because cognitive and metacognitive strategies can significantly help readers become autonomous and able to engage actively in the various events surrounding the act of reading. We chose hypertext due to the fact that this text format allows readers to choose their own reading paths. However, it requires strategic knowledge so that readers do not sink in the sea of information. For our theoretical framework, we used reading approaches to foreign language teaching (CARREL, 1995; HUDSON, 2007; LEFFA, 1999; MOITA LOPES, 1996), studies on online reading and the autonomous reader of hypertext (CHARTIER, 2002; COSCARELLI, 2010; LÉVY, 2004; MARCUSCHI, 2005; SNYDER, 1998; XAVIER, 2002) and works based on the teaching of cognitive and metacognitive strategies for hypertext reading (KONISHI, 2003; O'MALLEY; CHAMOT, 1993; SOLÉ, 1998). This research consists of a case study with participant observation. Thus, the researcher intervenes through instruction of hypertext reading strategies and, at the same time, investigates the process in which 8 learners use those strategies. The participants of this study were attending, at that time, technical high school classes in a federal institute located in the southeast of Goiás, Brazil. We conducted our research from September to December 2014. In general, the results of our research indicate that the teaching of cognitive and metacognitive strategies contributed to engage participants in self-monitoring activities of reading, providing them with possibilities to get an effective understanding of hypertexts in English. Our findings also revealed evidence that the participants showed an autonomous attitude toward reading hypertext in English.